Blockchain for Transforming International Trade: Bangladesh Perspective - S. M. Al Amin; Shakila Yasmin (International Journal of Supply Chain Management, 2022)
Blockchain is one of the key pillars of the fourth industrial revolution and blockchain become an enormous excitement in many industries including the international trade ecosystem. As we move forward to the fourth industrial revolution, the digitalization of the traditional international trade process is vital. Research on blockchain technology in the field of international trade is very limited. The purpose of this qualitative study is to look at the blockchain application in the field of international trade for Bangladesh perspective. To find out a comprehensive view of blockchain in the international trade ecosystem, in-depth primary interview with relevant stakeholders was taken in addition to analyzing secondary data. The study found that blockchain can transform many parts of the existing international trade process in Bangladesh including customs, trade document management, trade method, payment, transport document, certifications and combating fraudulent activities.